Vicarious violence and gender in the Andean Community: regulatory challenges with emphasis on the ecuadorian case - López Ruiz, Iliana; Maldonado Erazo, Elizabeth; Burbano Coral, Veronica (Ius Humani. Jornal do direito, 2025)
The article analyzes vicarious violence as an extreme and specific manifestation of gender-based violence, characterized by the use of sons and daughters as instruments to emotionally harm women. Through a legal-dogmatic and comparative law approach, the paper also examines Ecuador's regulatory gaps, progress and challenges in Andean countries, and international human rights law standards. To achieve the research objective, a methodology of legal and documentary analysis is employed, aimed at systematically studying the normative treatment of vicarious violence as a specific manifestation of gender-based violence. The approach is based on a comprehensive review of national and international normative sources, relevant constitutional jurisprudence, specialized doctrine, as well as recent legislative proposals related to the subject. It concludes that the autonomous recognition of this form of violence, together with the adoption of intersectional public policies with a gender perspective, is essential to guarantee effective protection for women, children, and adolescent victims.